1985
DOI: 10.1002/jccs.198500067
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Bridged Bimetallic Complexes. I. Copper(II) Complexes with Conjugated Diimine Ligands

Abstract: A series of binucleating Uganda with fully conjugated π‐systems have been synthesized. Homobinuclear copper(II) complexes of the form [(Cu(dien)ClO4)2L]‐(ClO4)2, where dien is diethylenetriamine and L is binucleating ligand, were prepared. Mononuclear complexes, with structure similar to that of the preceeding compounds, [Cu(dien)L′(ClO4)](ClO4) were synthesized as reference compounds. The infrared spectra, elctronic spectra and magnetic properties were studied. The inductive effect, steric effect and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
1990
1990

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The ligands, pyridyl ketimine, were prepared by the method of J.S. Walia et al 8 The solution EPR spectra of (1), (3), (5), (7) are shown in Fig. 2.…”
Section: Preparation Of Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligands, pyridyl ketimine, were prepared by the method of J.S. Walia et al 8 The solution EPR spectra of (1), (3), (5), (7) are shown in Fig. 2.…”
Section: Preparation Of Ligandsmentioning
confidence: 99%
“…Again, the appearance of spectra of (2), (4), (6) and (8) are identical with (I), (3), (5), and (7), respectively,so that they are not shown. The spectra of (1), (5) and (7) can be analyzed with a set of g values and hyper fine coupling constants with cylindrical symmetry. In the spectrum of (3), though quite different from the other three spectra, two small humps which correspond to the components of g and A are observed.…”
Section: Preparation Of Ligandsmentioning
confidence: 99%